THE IMPORTANCE OF GAME TECHNOLOGIES IN TEACHING ENGLISH TO ADULTS - Yarmatova, Dilrabo (Журнал иностранных языков и лингвистики, 2023)
The aim of the study is the theoretical substantiation and practical development of an invariant model of technology for organizing and conducting games in foreign language classes with adults based on linguistic material and simulating an authentic situation of communication. Research methods are complex. Among them, first of all, theoretical methods: analysis of psychological, didactic and methodological literature; analysis of the program for oral and written speech of the English language, observation and questioning, generalization of pedagogical experience; experimental: diagnostic methods, methods of processing experimental data. The results of the study is approved by efficiency of communicative games in foreign language classes as an integral element of the process of forming communicative skills which will increase both the level of communicative competence and the degree of proficiency in language material. The possibilities of using gaming technologies in teaching a foreign language to adult participants in the educational process are disclosed in detail. The main functions of games that are implemented in foreign language classes with adult students are analyzed: educational, motivational, diagnostic, correctional, organizational, developmental, educational, communicative, therapeutic, intercultural and interethnic communication, etc. The most common criteria underlying the development of a typology of gaming technologies in a foreign language lesson: type of activity, number of participants, purpose, degree of complexity, form of conduction, method of organization, orientation to the process or result, applied mechanisms.